Linking Women Farmer Perceptions and Knowledge of Soil Health to Climate-Smart Coffee Cropping Management - Handayani, Iin; Aprianto, Yudie; Ferguson, D; Widiastuti, Heppy (Journal of Smart Agriculture and Environmental Technology, 2024)
Coffee cropping is very sensitive to global warming, thus affecting coffee growers, particularly women farmers and their economies. As unpredictable weather continues to limit the suitability of the majority of traditional coffee-growing regions, women farmers are applying climate-smart agriculture (CSA) practices as a means of climate change mitigation and adaptation through healthy soil identification. Healthy soil is an important indicator that determines the  sustainability of coffee cropping under CSA practices. This study determined women farmers’ knowledge of soil health indicators and perspectives on CSA practices in the coffee cropping region of Sumatra, Indonesia. The qualitative analysis based on the interviews and focus group discussions from 90 women farmers revealed that the most common soil health indicators were soil color and soil organic matter, while the least common was soil ecology. The best climate-smart coffee cropping practices were from the agroforestry system and the least were observed in the long-term conventional tillage system. Over 80% of women farmers express a strong belief in the effectiveness of soil health indicators for implementing successful climate-smart farming methods. The majority of the women recognized the importance of the use of cover crops and strategies to prevent soil erosion. Knowledge about the benefits of soil amendments and intercropping was limited. Women farmers need to have more opportunities for training on various aspects in soil management as a mechanism for climate change adaptation as well as to improve their land for the sustainability of coffee production and their resilience in coffee farming. In order for the farm communities to make the full transition to CSA practices, the success factors and benefits of this management must be demonstrated to the coffee farmers.